Exploring Consumer Acceptance of Entomophagy: A Survey and Experiment in Australia and the Netherlands - Lensvelt, Eveline; Steenbekkers, L. (2014)
Insects are nutritious and suitable for human consumption. In this article an overview of research on consumer acceptance of entomophagy is given. This study furthermore provides insight into which factors are effective to influence consumer acceptance of entomophagy among Dutch and Australian participants. Based on the findings of this study, information about entomophagy and providing the participants with the opportunity to try insect food, both seem to be equally important when trying to positively influence their attitude toward entomophagy. The outcomes of this study show that "educating" consumers about entomophagy should be practiced in its broadest sense. Copyright © Taylor & Francis Group, LLC.